Dyadic teaching in nursing student education: A secondary analysis. Issue 3 (June 2022) - Irvine, Susan; Williams, Brett; McKenna, Lisa
Abstract: Problem: There is a lack of understanding of undergraduate nursing students' shared regulatory behaviours and metacognitive processes as they learn to teach in dyad. Insights into this pedagogical approach can provide the opportunity to re-evaluate the best approaches to learning in the collaborative learning space. Aim: The aim of this study was to explore the shared guidance and metacognitive and behavioural regulation of undergraduate nursing students involved in dyadic near-peer teaching. Method: Secondary qualitative data analysis was conducted on data collected from an earlier study of 14 interviews, which explored final year students undertaking dyadic near-peer teaching. Data were analysed using NVivo12 to identify categories of meaning. Finding: Two major categories and five subcategories evolved from the data, regulation of affective behaviours with associated subcategories of anxiety and self-doubt and shared guidance with subcategories of coregulation of cognition, metacognition, and critical thinking . Discussion: An important finding is that working in dyad provided a supportive environment for near-peer teaching, enhancing students' self-efficacy and metacognition ability through shared regulation by considering alternate perspectives, through shared understandings, and negotiating different viewpoints. Conclusion: It was identified that a dyadic approach in near-peer teaching supports metacognitive shared regulation and metacognitive growth; hence, influencing self-directed, long-life learners, a core nursing profession requirement.